Mastering your fears and phobias : therapist guide - Craske, Michelle G., 1959- (Treatments that work., 2006)
1. Introductory Information for Therapists. PART 1. Introduction to Specific Phobias and their Treatment. 2. Specific Phobias: Phenomenology. 3. Specific Phobias: How do they Develop?. 4. Specific Phobias: Learning About Your Specific Phobia. PART 2. General Principles of Treatment for Specific Phobias. 5. Specific Phobias: Developing a Treatment Plan. 6. Specific Phobias: Changing Thoughts. 7. Specific Phobias: Preparing for Exposure. 8. Specific Phobias: Specifics of Exposure. PART 3. Strategies and Ideas for Various Specific Phobias. 9. Overcoming Blood, Injection, and Injury Phobias. 10. O.